2021
DOI: 10.1590/s1678-4634202147238861
|View full text |Cite
|
Sign up to set email alerts
|

Injustiças e astúcias associativas nas ocupações das escolas públicas do Rio de Janeiro em 2016

Abstract: Resumo A partir de dados qualitativos construídos em pesquisa de campo realizada no ano de 2016 em cinco escolas públicas estaduais do Rio de Janeiro, são analisados os sentidos de injustiça que atravessam a escolarização pública estadual e os modos de atuar que conformam as ocupações das escolas e a experiência escolar atual. As análises conduzem a ampliar a definição da escola como arena pública e à percepção da multiplicidade de formas pelas quais os vínculos políticos se constituem, se rompem e se mantêm n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…18 corresponds to the 46-year periodicity of the wind and solar series, where a lag of 15 years approximately was observed between the two sinusoidal. The potential effects of climate change were not considered in this analysis (LEONI et al, 2017;Pinto, 2016). It was observed that, unlike wind dynamics, the solar source has a higher production moment, due to the expected behaviour within the fluctuations regime of approximately 15 years.…”
Section: Hybrid Energy System Of Caetité and Igaporãmentioning
confidence: 99%
“…18 corresponds to the 46-year periodicity of the wind and solar series, where a lag of 15 years approximately was observed between the two sinusoidal. The potential effects of climate change were not considered in this analysis (LEONI et al, 2017;Pinto, 2016). It was observed that, unlike wind dynamics, the solar source has a higher production moment, due to the expected behaviour within the fluctuations regime of approximately 15 years.…”
Section: Hybrid Energy System Of Caetité and Igaporãmentioning
confidence: 99%